45. Skin nerve α-synuclein deposits as possible new biomarker for Dementia with Lewy bodies. Issue 12 (December 2016) - Donadio, V.; Incensi, A.; Capellari, S.; Rizzo, G.; Pantieri, R.; Stanzani Maserati, M.; Devigili, G.; Eleopra, R.; Montini, F.; Baruzzi, A.; Liguori, R.
Abstract : The object of this study is to investigate whether: (1) phosphorylated α -synuclein (p-syn) deposits in peripheral nerves might represent a useful biomarker in dementia Lewy Body (DLB) helping to differentiate DLB from other forms of dementia; (2) small fiber neuropathy (SFN) may be part of DLB pathological picture contributing to autonomic dysfunctions. 20 well-characterized DLB patients (11 of them complaining autonomic symptoms particularly orthostatic hypotension) were studied together with 23 patients with dementia of different pathogenesis (Dementia without synuclein- DWS) including 13 patients fulfilling diagnostic criteria for Alzheimer's disease, 6 with Frontotemporal Dementia and 4 with vascular dementia. Twenty-five age-matched healthy subjects served as controls. Subjects underwent: nerve conduction velocities from the leg to evaluate large nerve fibers; skin biopsy from proximal (i.e. cervical) and distal (i.e. thigh and distal leg) sites to study small nerve fibers and deposits of phosphorylated α -synuclein, considered the pathological form of α -synuclein. P-syn was not found in any skin sample in DWS patients and controls but it was found in all DLB patients with a proximal-distal gradient with all patients positive in the cervical site. Patients complaining of autonomic symptoms showed higher widespread positivity of analyzed skin samples than patients without autonomic symptoms. Furthermore DLB patients showed a length-dependent SFN particularly important in patients complaining autonomic symptoms. Conclusions: (1) p-syn in peripheral nerves is a sensitive biomarker for DLB diagnosis helping to differentiate DLB from other forms of dementia; (2) SFN was part of DLB pathological picture contributing to induce autonomic symptoms.